2014
DOI: 10.1038/ncomms4617
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for oligomerization of auxin transcriptional regulators

Abstract: The plant hormone auxin is a key morphogenetic regulator acting from embryogenesis onwards. Transcriptional events in response to auxin are mediated by the auxin response factor (ARF) transcription factors and the Aux/IAA (IAA) transcriptional repressors. At low auxin concentrations, IAA repressors associate with ARF proteins and recruit corepressors that prevent auxin-induced gene expression. At higher auxin concentrations, IAAs are degraded and ARFs become free to regulate auxin-responsive genes. The interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
192
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(203 citation statements)
references
References 31 publications
4
192
0
2
Order By: Relevance
“…The essential residues at the dimer interface of PB1 were highly conserved in domain III−IV of Aux/ IAA and ARF family proteins, suggesting that they would be important for oligomerization. Indeed, mutation of the conserved residues has recently allowed for determination of the crystal structure of domain III−IV in ARF family proteins (14,15). Here we report, to our knowledge, the first solution structure of domain III−IV of Arabidopsis Aux/IAA17 (IAA17), and characterize the Significance Auxin is the central hormone that governs diverse developmental processes in plants.…”
mentioning
confidence: 84%
“…The essential residues at the dimer interface of PB1 were highly conserved in domain III−IV of Aux/ IAA and ARF family proteins, suggesting that they would be important for oligomerization. Indeed, mutation of the conserved residues has recently allowed for determination of the crystal structure of domain III−IV in ARF family proteins (14,15). Here we report, to our knowledge, the first solution structure of domain III−IV of Arabidopsis Aux/IAA17 (IAA17), and characterize the Significance Auxin is the central hormone that governs diverse developmental processes in plants.…”
mentioning
confidence: 84%
“…A crystal structure of an ARF bound to an ER AuxRE showed that the 15-18 bp spacing allowed the bound ARF homodimer to stabilize through interaction of the ARF dimerization domain (DD) (Boer et al, 2014). Similarly, the DR spacing preference may be explained by stabilizing interactions through a second dimerization domain, the III/IV domain ( Figure 6B) (Nanao et al, 2014). Importantly, although substantial evidence supports a role for motif dimers in ARF binding and auxin response regulation, no comprehensive model yet exists to explain or predict ARF binding site preferences (Farcot et al, 2015).…”
Section: Cooperative Binding Of Arf Homodimers At Phased Motif Repeatsmentioning
confidence: 99%
“…We also identified novel binding events at IR repeats, which showed similar spacing preferences to those seen for ER-TGTC repeats but had only two spacing groups (15-16 and 25-27 bp). To explain homodimer binding at this third repeat type, we propose a model in which a third isoform of the ARF5 homodimer, with interactions between positively and negatively charged sides of the III/IV dimerization domain (Nanao et al, 2014), stabilizes the complex at specific spacing of the IR-TGTC ( Figure S5C). To summarize, we observed three repeat-specific patterns of ARF binding that may be explained by three different ARF dimerization models.…”
Section: Cooperative Binding Of Arf Homodimers At Phased Motif Repeatsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inherent modularity of the ARC lends itself to adding additional layers of complexity and quantitative analysis of other challenging features of auxin response, such as feedback or higher-order complexes between ARFs and IAAs. Indeed, recent structural studies indicate the potential for higher-order ARF-IAA complexes than previously suspected (37)(38)(39). ARC Sc may be a useful tool for quantifying the impact of this structural complexity on response dynamics.…”
Section: Significancementioning
confidence: 95%